2022
DOI: 10.1097/j.jcrs.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contact lens–assisted and transepithelial corneal crosslinking with standard epithelium-off crosslinking for progressive keratoconus: 24-month clinical results

Abstract: To compare the outcomes of contact lens-assisted corneal crosslinking (CACXL) and transepithelial CXL (TECXL) with standard epithelium-off (epi-off) CXL for progressive keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…In a study evaluating 2-year follow-up, significant changes were observed in the CACXL groups in Kmax, simulated keratometry and SE, with larger reduction in Kmax compared with standard epi-off CXL, although this could be attributable to higher baseline Kmax in the CACXL group. 55 No complications were observed.…”
Section: Contact Lens-assisted and Smile Lenticule-assisted CXLmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study evaluating 2-year follow-up, significant changes were observed in the CACXL groups in Kmax, simulated keratometry and SE, with larger reduction in Kmax compared with standard epi-off CXL, although this could be attributable to higher baseline Kmax in the CACXL group. 55 No complications were observed.…”
Section: Contact Lens-assisted and Smile Lenticule-assisted CXLmentioning
confidence: 89%
“…A review by Srivatsa et al54 highlights the safety profile in 4 studies totaling 69 eyes with up to 1-year follow-up, showing no difference in demarcation line depth and endothelial cell density to other CXL protocols. In a study evaluating 2-year follow-up, significant changes were observed in the CACXL groups in Kmax, simulated keratometry and SE, with larger reduction in Kmax compared with standard epi-off CXL, although this could be attributable to higher baseline Kmax in the CACXL group 55. No complications were observed.…”
Section: Contact Lens-assisted and Smile Lenticule-assisted CXLmentioning
confidence: 97%
“…S. Srivatsa и соавт. подчеркнули профиль безопасности в 4 исследованиях с участием 69 глаз в течение 1 года наблюдения, при этом не было отличий в глубине демаркационной линии и плотности эндотелиальных клеток по сравнению с другими протоколами КРК [30,31]. Кроме того, при разработке КРК в сочетании со SMILE также была предпринята попытка увеличить толщину роговицы путем размещения донорской лентикулы в роговице перед облучением.…”
Section: кросслинкинг в комбинации с контактными линзами и лентикулойunclassified